Engineering Foods for Bioactives Stability and Delivery - Roos, Yrjö H.; Livney, Yoav D. (Springer New York : Imprint: Springer, 2017)
This book introduces recovery and stabilization of common bioactive materials in foods as well as materials science aspects of engineering stable bioactive delivery systems. The book also describes most typical unit operations and processes used in recovery and manufacturing of food ingredients and foods with stabilized bioactive components. The 15 chapters of the book discuss in detail substances that need to be protected and delivered via foods and beverages to achieve good stability, bioavailability and efficacy. Dedicated chapters present current and novel technologies used for stabilization and delivery of bioactive components. The material included covers formulation, stability, digestive release, bioaccessability and bioavailability. The text features a special emphasis on the materials science and technological aspects required for stabilization and successful production of foods with bioactive components. Consumer demand for healthier, yet satisfying food products is posing increasingly tough challenges for the food industry. Scientific research reveals new bioactive food components and new functionalities of known components. Food materials science has also developed to a stage where food materials can be designed and produced to protect sensitive components for their delivery in complex food products. Such delivery systems must meet high safety and efficacy requirements and regulations, as well as economic viability criteria and consumer acceptance.- Resumé vydavatel
Keywords: potravinářská biochemie; biotechnologie; potraviny; biologicky aktivní látky; food biochemistry; biotechnology; foodstuffs; bioactive compounds; elektronické knihy; sborníky; electronic books; papers of several authors